Towards harmonisation of the ASEAN contract law: the legal treatment of unfair consumer contract terms among selected ASEAN member states - Azimon Abdul Aziz,; Suzanna Mohamed Isa,; Sakina Shaik Ahmad Yusoff,; Ong, Tze Chin (FEP, 2011)
The rise of standard form contracts and the use of unfair terms to deprive consumers from their rights have indeed inspired the law in many countries to react against the increasing decline of the individual’s capacity to make free and rational choice. The legal development in this area illustrates the role of contract law, that is, to develop criteria and procedures through which contractual fairness can be assured. The development of contract laws throughout the Southeast Asian region is impacted by the tremendous historical and social diversity among the various countries, as demonstrated by the Malaysian, Singaporean and Bruneian contract laws, which reflect English common law due to historical development. However, countries such as Indonesia have been profoundly affected by long periods of civil law influence. The experience of the common law countries of the ASEAN member states in controlling the use of unfair terms in consumer contracts demonstrate a different regime of protection as opposed to the civil law countries. Harmonisation of ASEAN contract laws is essential for the regional cooperation of ASEAN countries in order to accelerate the economic growth, social progress and cultural development of the region. Bringing harmony between various contract laws of ASEAN countries would enhance economic prosperity as the laws of contract serve the economical and cultural values of society, in particular, consumer protection. Adopting the content analysis method, this paper aims at exploring the legal treatment of unfair terms in consumer contracts among the selected ASEAN member states. The paper will discuss and analyse the legislative provisions on unfair terms in Singapore, Brunei and the Philippines, focusing both on the legislative provisions as well as the judicial treatment of these terms. An analysis in the legal treatment in these three countries will then be undertaken in respect of harmonizing ASEAN contract law. The legal regime of all three countries reflects that the statutory control of exemption clauses in Singapore, Brunei and Philippines has taken many forms, however, since there are common features in the legislation, harmonizing it in respect of consumer protection can be achieved by reasonable compromises among the member states.